Teaching Convergence in 21st Century Undergraduate Agricultural Communication: A Pilot Study of Backpack Multimedia Kits in a Blended, Project-Based Learning Course - Jamie Loizzo; Abigail Borron; Amanda Gee; Peggy A. Ertmer (Journal of Applied Communications, 2016)
Twenty-first century agricultural communication students are expected to have an increasingly diverse set of skills when they graduate.Expertise is expected in: writing, editing, design, marketing, media relations, event planning, interpersonal communication, digital development, e-publications, online video, mobile applications, podcasting, and social media.This expansion of needed skills is due in no small part to the proliferation of communication channels and convergence of media platforms today. In order to continue preparing students for professions in agricultural communication, it is imperative that the curricula reflect current industry needs and available technology. In this article, one approach for expanding curricula to incorporate these newer technologies by implementing backpack multimedia journalism kits for science communication is discussed. The kits were developed to address these criteria: 1) students needed opportunities to gain a variety of broad technological skills, 2) the technology had to be mobile and cost effective, and 3) the technology needed to be able to produce a variety of content across a variety of platforms. The mobile multimedia kits included iPad-minis and video accessories. Through an agricultural communication blended-learning, project-based undergraduate course, the authors tested the effectiveness of the kits, as well as researched students’ perceptions and experiences with the course design and mobile communication technologies. The results of the study showed students valued the selected technology and gained targeted video production skills. Although students’ liked the course design, they experienced challenges with course requirements, time management, and using the technological audio recording components.
Keywords: Agriculture Communication; Backpack Journalism; Convergence; iPad; Multimedia; Project Based Learning; Undergraduate